Laser micro-texture formation mechanism based on modified heat-mass transfers and hydrodynamic models. (15th September 2022) - Zhang, Jing; Zhang, Song; Chen, Guangyu; Jia, Zhe; Qu, Yifei; Guo, Ziyu
Highlights: Recoil pressure is the key factor for spattering and expansion of molten pool. Intensity of vortex generated at groove bottom is greater than that at the side. More recast layer and redeposition of melt result in a poor surface roughness of groove. Surface roughness of groove gradually decreased with increasing laser moving speed. Abstract: Laser surface texturing is considered as a novelty and feasible technology to fabricate some micro-feature due to the non-contact, high precision and processing efficiency. However, it is difficult to deeply understand the material removal mechanism and predict the surface topography due to a confined heat-affected zone and extremely short time in the laser machining process. In this research, based on the mixed phase theory and level-set method, a modified heat-mass transfer and hydrodynamic model was proposed for deeply analyzing the influence of various physical factors such as recoil pressure, buoyancy, surface tension, gravity and thermal-mass transport on the material removal and micro-texture topography evolution at a mesoscale level. The analysis of hydrodynamic behaviors and temperature fields of the molten pool indicated that the melts sputtering and molten pool expansion caused by the recoil pressure was the dominant factor responsible for micro-texture formation during laser action. The reflux induced by the surface tension and gravity as well as the residual effect of the melts flowing upward were the main factors of the occurrence of a vortex during the molten pool cooling. Finally, the effects of laser parameters on the micro-feature topography were discussed based on the experiments and simulation model. The diameter and depth of the hole as well as the width and depth of the groove gradually increased with increasing frequency and pulse duration. The laser moving speed had less effect on the width of the groove, but it had great effect on the surface roughness of the groove. This work can be beneficial to understand the material removal mechanism and provide a guide for the parameters optimization of laser processing at a mesoscale level. Graphical abstract: Image, graphical abstract